Heating water using the hot air of condensers and tubes-and-fins heat exchangers – Thermodynamic modeling and parametric study with economic and environmental insights - Ahmad Al Takash; Jalal Faraj; Sary Awad; Hicham El Hage; Mahmoud Khaled (Unconventional Resources)
Recovering the waste heat from condensers of Heating, Ventilating and Air Conditioning (HVAC) is taking big importance nowadays in the building energy management sector. Advances in this area are still needed due to the high amount of heat released from the condensers versus the low effectiveness of and high volume of the heat recovery medium. As compact and high effectiveness heat exchangers, tubes and fins heat exchangers constitute a potential candidate to overcome the concerns. In this context, the primary goal of this research is to investigate the effect of employing tubes and fins heat exchangers to recover heat from the condenser. To accomplish this goal, a thermodynamic modeling, in addition to analytical approach of the system performance were introduced. Then, a parametric study was performed to examine the effect of the mass flow rate of air and water on the suggested heat recovery system. Finally, economic, and environmental insights based on the energy analysis are presented. It was observed that increasing the mass flow rate from 0.417 kg/s to 2.5 kg/s enhanced the power output from 14.5 kW to 15.1 kW. Similarly, lowering the water inlet temperature from 35 °C to 15 °C increased the power output from 11.28 kW to 15 kW The study highlighted the notable savings with various COP and cooling load, particularly at low COP and a cooling load of 30 kW. Moreover, the investigation revealed that maintaining a constant COP of 2 and increasing cooling loads contributed to higher CO2 emission reduction, ranging from 3.8 kg at 5 kW to 16.5 kg at 25 kW. The findings confirm that the suggested heat recovery system is effective in reducing energy waste and minimizing environmental impact. Finally, it was observed that the proposed system has 95 % capacity of heat recovery.